The Religious Value in Helvy Tiana Rosa and Benny Arnas’ Hayya - Yulianti Yulianti; Supriyono Supriyono; Akhmad Sutiyono; Aksendro Maximilian (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
The purpose of this research was to find out and to analyse the religious values which were available in a literary work (novel) entitled